2006
DOI: 10.1001/jama.296.21.jed60074
|View full text |Cite
|
Sign up to set email alerts
|

Challenges for Improving Medication Adherence

Abstract: OR CHRONIC MEDICAL CONDITIONS, SUCH AS HYPERcholesterolemia and hypertension, a wide and persistent separation exists between evidence-based recommendations and the actual care patients receive. 1 Reasons for this gap are not always clear, but some components are obvious, including failing to identify patients in need of treatment, not properly initiating treatment, failing to provide proper drugs at proper doses, and neglecting to involve the patient in the choices inherent in care. Lack of persistence with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 17 publications
2
44
0
4
Order By: Relevance
“…These students then may increase the amount of time spent counseling, which has been shown to improve patient outcomes. [28][29][30][31][32] Students also need to be aware of how the healthcare system functions in order to better understand the experiences of their patients. Many students have had limited experience as a "patient," since younger adults make American Journal of Pharmaceutical Education 2011; 75 (8) Article 158.…”
Section: Discussionmentioning
confidence: 99%
“…These students then may increase the amount of time spent counseling, which has been shown to improve patient outcomes. [28][29][30][31][32] Students also need to be aware of how the healthcare system functions in order to better understand the experiences of their patients. Many students have had limited experience as a "patient," since younger adults make American Journal of Pharmaceutical Education 2011; 75 (8) Article 158.…”
Section: Discussionmentioning
confidence: 99%
“…La non aderenza alla terapia per la prevenzione secondaria della cardiopatia ischemica è perciò una sfida importante per la sanità [34] e la fase successiva alla dimissione rappresenta il "periodo vulnerabile," in particolare per gli anziani che, assumendo più frequentemente la politerapia, hanno più probabilità di presentare problemi legati ai farmaci [35].…”
Section: Conclusioniunclassified
“…Infatti, cardine dell'intervento non sono solo le prescrizioni, ma la terapia di sostegno che ogni operatore, coinvolto nella cura dei pazienti, deve offrire perché essi accettino di proseguire le indicazioni terapeutiche che alla lunga non sono di semplice realizzazione [8,27,35].…”
Section: Conclusioniunclassified
“…98,99 However, a recent systematic review of interventions to enhance patient adherence to medications concluded current methods are complex, laborintensive, and not predictably effective, therefore, not able to be used in the clinical setting. 100 Simple pill reminders such as plastic pill boxes and calendars have demonstrated effectiveness in some types of medication adherence studies, however limited evidence is available when the complexity of the regimen with oral antineoplastic agents and further study is needed.…”
Section: Strategies To Improve Adherencementioning
confidence: 99%